2013
DOI: 10.1177/0363546513502459
|View full text |Cite
|
Sign up to set email alerts
|

Complications After Anatomic Fixation and Reconstruction of the Coracoclavicular Ligaments

Abstract: Anatomic procedures to treat disrupted CC ligaments using either CFBs or TGs resulted in an overall complication rate of 27.1% (16/59). Construct survivorship was calculated to be 86.2% at 12 months and 83.2% at 24 months. Good to excellent outcomes could only be reported in those patients who did not have a complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
196
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(204 citation statements)
references
References 33 publications
3
196
1
4
Order By: Relevance
“…There is even less evidence available to dictate the best strategy for revision following failed AC joint [18]. In their series, the overall construct survivorship without complications was 86 and 83 % at 12 and 24 months, respectively [18].…”
Section: Complications From Operative Treatment Of Acromioclavicular mentioning
confidence: 98%
“…There is even less evidence available to dictate the best strategy for revision following failed AC joint [18]. In their series, the overall construct survivorship without complications was 86 and 83 % at 12 and 24 months, respectively [18].…”
Section: Complications From Operative Treatment Of Acromioclavicular mentioning
confidence: 98%
“…Good to excellent clinical results have been reported after reconstruction of the coracoclavicular ligaments with soft-tissue grafts 10 ; however, complications including graft rupture, hardware failure, and fracture of the clavicle or coracoid through bone tunnels are a concern. 4 A study conducted by Spiegl et al 7 showed a significant decrease in clavicle strength when bone tunnels were created for graft passage. However, using a single 3-mm bone tunnel placed through the distal clavicle and the coracoid base did not result in a change in clavicular load to failure when compared with the intact state.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal management of grade III injuries remains controversial, with many surgeons performing surgery acutely in highlevel athletes and manual laborers. [3][4][5] The original Weaver-Dunn method of AC joint reconstruction has been modified over the past 4 decades, most recently with anatomic coracoclavicular ligament reconstruction with soft-tissue grafts, which have shown superiority on biomechanical testing. 6 Bone tunnels through the clavicle are commonly used to reconstruct the coracoclavicular ligaments; however, they have been associated with a significant decrease in clavicle strength with a subsequent increase in the risk for postoperative fracture.…”
mentioning
confidence: 99%
“…Erwähnenswert ist zudem, dass bei dem arthroskopisch assistierten Verfahren mit "tight rope" die Nachbehandlung im Allgemeinen sehr restriktiv gehandhabt wird. Hier wird von den Operateuren eine 6-wöchige Ruhigstellung in der Schlinge mit nur passiver Beweglichkeit empfohlen [11,17]. Im Gegensatz hierzu erlaubt die Versorgung mit Hakenplatte eine relativ rasche freie Beweglichkeit.…”
Section: Hakenplatte Vs Fadenbasierte Stabilisierungunclassified